Mutational Analysis of DNASE I Gene in Diabetic Patients - Hussain, Nageen; Kayani, Hateem Zafar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
<span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The main aim is to analyze the mutations of DNASE I gene in diabetic patients.<span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">A total of 120 diabetes patients and 120 controls were sampled. The total number of male diabetic patients included in the study was 79 (66%) while female patients were 41 (34%) in number. <span style="line-height: 115%; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Exon 8 of the DNASE I gene was amplified by using thermocycler. The possible band of interest was located at 165 base pairs. Two samples showed similar missense mutations at 127th position of exon 8 which replaced amino acid Arginine (Arg) to Glutamine (Gln). All controls showed no mutations. The association of diabetes with different levels of blood pressure and body mass index (BMI) were found to be significant.